How Multidimensional Health Locus of Control predicts utilization of emergency and inpatient hospital services. (March 2017) - Mautner, Dawn; Peterson, Bridget; Cunningham, Amy; Ku, Bon; Scott, Kevin; LaNoue, Marianna
Health locus of control may be an important predictor of health care utilization. We analyzed associations between health locus of control and frequency of emergency department visits and hospital admissions, and investigated self-rated health as a potential mediator. Overall, 863 patients in an urban emergency department completed the Multidimensional Health Locus of Control instrument, and self-reported emergency department use and hospital admissions in the last year. We found small but significant associations between Multidimensional Health Locus of Control and utilization, all of which were mediated by self-rated health. We conclude that interventions to shift health locus of control may change patients' perceptions of their own health, thereby impacting utilization.